Clinical Complications Associated with Spinal Cord Injury: A Narrative Review - Mohammed, Ibrahim; Ijaz, Sahar; Gholaminejhad, Morteza; Hassanzadeh, Gholamreza (Journal of Contemporary Medical Sciences, 2021)
Spinal cord injury (SCI) is a neuro-destruction occurred from a complete or incomplete, traumatic or non-traumatic that results in degeneration, structural, biochemical, and physiological changes of tissue. SCI is a clinical problem associated with impairments in different aspects of the patient's life. The pathophysiology of SCI involves a primary phase that directly disrupts axons, cell membranes, and blood vessels. This primary phase is followed by a secondary phase involving vascular dysfunction, ischemia, excitotoxicity, oxidative stress, inflammation, and cell death. If this second phase isn't managed, it will result in many pathological processes that will cause several clinical complications. The aim of rehabilitation and other treatments is to enhance the functional level and to reduce secondary morbidity as well as improve the quality of health of the patient. SCI results in different complications in different organs of the individual. Early diagnosis, treatment, and prevention of complications in SCI patients are very important for limiting these complications. This review was carried out in order review the data about clinical complications associated with SCI, including multiple organ dysfunction, systemic inflammation, immune suppression, neurogenic shock, autonomic dysreflexia, orthostatic hypotension, temperature regulation, sweat secretion, respiratory complications and dysphagia, thromboembolism, urinary system, reproductive system, skeletal muscle, bone, liver, spleen and gastrointestinal tract. The purpose of this narrative review is to provide knowledge on the SCI complications, sign and symptoms, risk factors prevention and treatment of complications caused by SCI.